2010
DOI: 10.1111/j.1463-6395.2008.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross anatomy of the musculature and a new description of the reproductive system of Tanaisia bragai and Tanaisia inopina (Trematoda: Eucotylidae) analysed by confocal laser scanning microscopy

Abstract: D'ávila, S., Manso, P. P. A., Bessa, E. C. A., Rodrigues, M. L. A. and Dias, R. J. P. 2010. Gross anatomy of the musculature and a new description of the reproductive system of Tanaisia bragai and Tanaisia inopina (Trematoda: Eucotylidae) analysed by confocal laser scanning microscopy. -Acta Zoologica (Stockholm) 91: 139-149Confocal scanning laser microscopy has become an important tool to clarify the organization of the musculature and innervation, as well as the morphology of the reproductive and alimentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Additionally, this staining technique is simple and rapid in comparison with known protocols, which are time consuming and consist of several steps of sample preparation. Staining of one parasite by utilizing available protocols can take more than two days and the procedure is appropriate for staining of parasite-specific tissues (Stewart et al, 2003; Davila et al, 2010; Krupenko, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this staining technique is simple and rapid in comparison with known protocols, which are time consuming and consist of several steps of sample preparation. Staining of one parasite by utilizing available protocols can take more than two days and the procedure is appropriate for staining of parasite-specific tissues (Stewart et al, 2003; Davila et al, 2010; Krupenko, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some results obtained through confocal microscopy studies have confirmed evolutionary relationships. As an example, several descriptions of the muscle system (Mair et al 1998b(Mair et al , 2000Kumar et al 2003;Šebelova et al 2004;Terenina et al 2006;D'Ávila et al 2010) have strengthened the idea that the organization of the somatic musculature is conserved among the digeneans, as stated by Šebelova et al (2004). The pattern of vitellogenesis seems to be even more conserved among digeneans, monogeneans, cestodes and free-living neophoran (Swiderski & Xylander 2000;D'Ávila et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…As an example, several descriptions of the muscle system (Mair et al 1998b(Mair et al , 2000Kumar et al 2003;Šebelova et al 2004;Terenina et al 2006;D'Ávila et al 2010) have strengthened the idea that the organization of the somatic musculature is conserved among the digeneans, as stated by Šebelova et al (2004). The pattern of vitellogenesis seems to be even more conserved among digeneans, monogeneans, cestodes and free-living neophoran (Swiderski & Xylander 2000;D'Ávila et al 2010). In addi-tion, the morphological characterization of the musculature of tubular organs and attachment apparatus has supported some functional interpretations (Mair et al 1998b(Mair et al , 2000Šebelova et al 2004;D'Ávila et al 2010).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations